Struniak w okolicy kości krzyżowej u 47 - letniej pacjentki - opis przypadku = Chordoma in the sacral spine in an 47-year-old woman - case report - Kamila Woźniak; Dorota Ratuszek-Sadowska; Agnieszka Nowacka; Maciej Śniegocki (Kazimierz Wielki University, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Nowacka Agnieszka, Śniegocki Maciej. Struniak w okolicy kości krzyżowej u 47 - letniej pacjentki - opis przypadku = Chordoma in the sacral spine in an 47-year-old woman - case report. Journal of Education, Health and Sport. 2016;6(9):261-267. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61686 http://ojs.ukw.edu.pl/index.php/johs/article/view/3802       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Struniak w okolicy kości krzyżowej u 47 - letniej pacjentki - opis przypadku   Chordoma in the sacral spine in an 47-year-old woman - case report   Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Agnieszka Nowacka1, Maciej Śniegocki1   • 1.        Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • 2.        Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu     Streszczenie   Struniaki (łac. chordoma) są rzadkimi, histologicznie łagodnymi, lecz klinicznie złośliwymi nowotworami szkieletu osiowego. Mogą powstać w dowolnym miejscu w linii środkowej ciała, gdzie istniała struna grzbietowa (np. stok, nosogardziel, siodło i okolica okołosiodłowa, otwór wielki kręgi i okolica krzyżowo-ogonowa). Struniaki to wolno rosnące nowotwory, wykazujące miejscową agresywność w stosunku do kości i tkanek miękkich. Struniaka po raz pierwszy opisał w 1856 roku Virchow i Luschke. Z kolei w 1858 roku Muller stwierdził, że nowotwór może pochodzić z pozostałości embrionalnych prymitywnej struny grzbietowej tzw. chorda dorsalis. Autorzy przedstawiają opis przypadku klinicznego leczonego operacyjne w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy z rozpoznanym w badaniu histopatologicznym struniakiem.   Słowa kluczowe: struniak, chrodoma, nowotwór, szkielet osiowy, neurochirurgia.     Abstract   Chordomas are rare, histologically benign but clinically malignant tumors of the axial skeleton. They can occur anywhere in the midline of the body where there notochord (clivus, nasopharynx, saddle and surroundings parasellar, the foramen vertebrae and surroundings sacral area). Chordomas are slow-growing cancer, showing local aggressiveness relative to bone and soft tissue. Chordoma was first described in 1856 by Virchow and Luschke. In turn, in 1858 Muller found that the cancer can come from embryonic remnants of the primitive notochord called chorda dorsalis. The authors present a clinical case operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz histopathological diagnosed with chordoma.   Key words: chordoma, cancer, axial skeleton, neurosurgery.